2023
DOI: 10.1021/acs.cgd.3c00072
|View full text |Cite
|
Sign up to set email alerts
|

Energetic Coordination Polymers Based on Copper Furazans and 1,2,3-Triazoles: Tuning the Oxygen Balance with Nitramino Functionalities

Abstract: Four novel energetic complexes comprising furazan/nitramino groups were synthesized through a simple hydrothermal method. Owing to the introduction of an oxygencontaining nitramino group, Cu(DNAF)(NH 3 ) 3 (ECP-1), Cu-(DNAF)(H 2 O) 3 (ECP-2), Cu(ANFZ) 2 (H 2 O) 5 (ECP-3), and Cu 2 (TA) 2 (H 2 O) 6 (ECP-4) (DNAF = 4,5-dinitraminofurazan, ANFZ = 4-amino-3-nitraminofurazan, TA = 5-nitro-4-nitramino-1,2,3-triazole) possess relatively high oxygen contents and oxygen balance, indicating efficient energy release duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…11,12 Recently, there has been a surge in the number of new energetic compounds based on nitrogen and oxygen-rich heterocyclic ring systems like azoles, oxadiazoles, pyrazine, tetrazene, etc. 13–22 Energetic materials with such nitrogen-based heterocyclic rings as their backbone are highly endothermic and considered environmentally friendly as they release non-toxic dinitrogen (N 2 ) gas after their decomposition. Therefore, recently, several heat-resistant explosives based on polynitrobenzene moieties connected to nitrogen-rich heterocyclic rings have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Recently, there has been a surge in the number of new energetic compounds based on nitrogen and oxygen-rich heterocyclic ring systems like azoles, oxadiazoles, pyrazine, tetrazene, etc. 13–22 Energetic materials with such nitrogen-based heterocyclic rings as their backbone are highly endothermic and considered environmentally friendly as they release non-toxic dinitrogen (N 2 ) gas after their decomposition. Therefore, recently, several heat-resistant explosives based on polynitrobenzene moieties connected to nitrogen-rich heterocyclic rings have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…7 Moreover, 1,2,3-triazoles find a myriad of applications as approved pharmaceuticals or promising drug candidates with a broad range of biological activities, 8 as effective inhibitors of the corrosion process of metals or their alloys, 9 and as components of functionalized polymeric materials 10 or high-energy substances. 11 However, closely related 1,2,3-triazole 1-oxides are far less explored in spite of their structural similarity. Meanwhile, several theoretical studies of triazole oxide derivatives have been performed, which showed their potential application as energetic materials.…”
Section: Introductionmentioning
confidence: 99%